2006
DOI: 10.4049/jimmunol.176.3.2007
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Intracerebral and Peripheral Blood Immune Responses in Vietnamese Adults with Tuberculous Meningitis: Diagnostic Value and Relationship to Disease Severity and Outcome

Abstract: Tuberculous meningitis (TBM) is the most devastating form of tuberculosis. Both intracerebral and peripheral blood immune responses may be relevant to pathogenesis, diagnosis, and outcome. In this study, the relationship between pretreatment host response, disease phenotype, and outcome in Vietnamese adults with TBM was examined. Before treatment, peripheral blood IFN-γ ELISPOT responses to the Mycobacterium tuberculosis Ags ESAT-6, CFP-10, and purified protein derivative (PPD) were a poor diagnostic predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 32 publications
4
45
1
2
Order By: Relevance
“…34À36 Previous immunologic studies in our cohort of TBM patients found that cerebrospinal fluid (CSF) interleukin-6 concentrations were associated with the most severe disease. 37,38 Given the central role of TLR2 in mediating immune responses, it is possible that TLR2 genetic variants differentially regulate inflammatory pathways and influence the intra-cerebral inflammatory responses that determine severity and outcome of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…34À36 Previous immunologic studies in our cohort of TBM patients found that cerebrospinal fluid (CSF) interleukin-6 concentrations were associated with the most severe disease. 37,38 Given the central role of TLR2 in mediating immune responses, it is possible that TLR2 genetic variants differentially regulate inflammatory pathways and influence the intra-cerebral inflammatory responses that determine severity and outcome of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The blood-brain barrier is often damaged, reflected by a raised CSF:serum albumin ratio [31][32][33]. In HIV-negative patients, the concentration of lactate and protein are positively associated with TBM grade and clinical outcome [31]. Lactate is produced in hypoxic tissues, and high levels in CSF may reflect ischemic events in the brain.…”
Section: Immunologymentioning
confidence: 99%
“…Typically in TBM, the CSF shows a lymphocytic pleiocytosis and inflammatory indices (including TNF, IFN-g, IL-8, IL-10, matrix metalloproteinases, and their corresponding tissue inhibitors) are usually raised in the CSF in the acute phase of disease. The blood-brain barrier is often damaged, reflected by a raised CSF:serum albumin ratio [31][32][33]. In HIV-negative patients, the concentration of lactate and protein are positively associated with TBM grade and clinical outcome [31].…”
Section: Immunologymentioning
confidence: 99%
“…Misra et al studied both children and adults and identified stage, age, focal weakness, cranial nerve palsies, and hydrocephalus as predictors of mortality at 3 months (133). Interestingly, features such as presenting intracranial pressure (184), cytokines in the CSF (198), isoniazid or streptomycin resistance (214), and M. tuberculosis genotype (122) have been shown not to be predictive of a poor outcome.…”
Section: Prognosis and Outcomesmentioning
confidence: 99%